Implementation of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) and Law No. 5 of 1990 in Law Enforcement Efforts and Guarantees of Environmental Rights in Gunung Leuser National Park, Indonesia - Lubis, Muhammad Ikhsan (JILS (Journal of Indonesian Legal Studies), 2017)
Indonesia is renowned for its abundant natural resources and vast biodiversity. However, Indonesia also has wildlife species that are most vulnerable to the threat of extinction. Illegal wildlife trade poses a serious threat to the preservation of wildlife in Indonesia. Wildlife illegally traded based on facts found in the field is mostly a catch from nature, not from captive breeding. Gunung Leuser National Park (Taman Nasional Gunung Leuser, TNGL) as one of the national parks in Indonesia faces problems in the protection of this wildlife. This is triggered by the process of industrialization, illegal logging activities and crimes against protected wildlife. Wildlife protection in Indonesia and internationally is regulated legally through Law No.5 of 1990 and internationally through the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). The role of local government, BKSDA TNGL, and related agencies in suppressing the extinction rate provides an understanding to the community of TNGL conservation areas, in particular, to reduce conflicts and clearance of plantation land by utilizing the concept of environmentally sustainable development as well as providing the mitigation measures.